Chirurgia endoskopowa oczodołu - Sieśkiewicz, Andrzej; Łysoń, Tomasz; Obuchowska, Iwona; Napora, Katarzyna; Rogowski, Marek; Turek, Grzegorz; Mariak, Zenon (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Thanks to continuous improvement of instrumentarium, methods of imaging and intraoperative neuronavigation, endoscopic techniques are increasingly used for management of intraorbital pathologies. The aim of the study was to present, basing on own experience, the virtues and limitations of endoscopic transnasal surgery in the diagnosis and treatment of orbital pathologies. This article contains a review of endoscopic treatment of lacrimal duct stenosis, evacuation of inflammatory lesions and benign tumors penetrating the orbit from the adjacent sinuses, management of primary intraorbital tumors, Graves-Basedov orbitopathy and posttraumatic lesions of the optic nerves. Both own experience and data from the relevant literature indicate that intraorbital inflammatory lesions can nowadays be effectively treated by means of endoscopy whereas purely endoscopic removal of intraorbital tumor still remains rare because is technically demanding and requires high experience in this type of surgery. In case of malignancies endoscopy may be used for diagnostic purposes and/ or as a method supporting conventional external surgical approaches.